The Oak Ridges Moraine of Southern Ontario: A Ground-water Resource at Risk - Howard, Ken; Eyles, Nicholas; Smart, Philip; Boyce, Joseph; Gerber, Richard; Salvatori, Sean; Doughty, Mike (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1995)
Summary Protection of ground-water resources is an emerging theme in many urbanareas. In south-central Ontario, the Oak Ridges Moraine (-1400 km2) is a promi-nent glacial moraine complex on the rapidly urbanizing northern margin of the Greater Toronto Area and constitutes a major regional aquifer system.Given the pre-eminent economic importance of the region, the ground-water resource can be argued to have provincial significance, and there is much current debate regarding the impact of urbanization and other anthropogenic activities on ground-water quality and supply. Particular issues are the degree of acceptable future development and the definition of the most environmentally and hydrogeologically sensitive areas.This paper reviews what is currently understood of the geology and hydro-geology of the Oak Ridges Moraine, and provides an overview of quantitative modelling studies.